2013
DOI: 10.14419/ijaes.v1i1.771
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intellectual capital on financial performance in the pharmaceutical industry in Iran

Abstract: In the era of knowledge-based economy, organizations make use of two distinct sources for value creation and profit, i.e., tangible resources and or intangible resources. On the other hand, it is believed that intellectual capital could be better than the material and physical capital in explaining financial performance indicators of companies. Regarding this background, the present research, through an investigation done on the performance of 22 pharmaceutical companies in the period of [2004][2005][2006][200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…2021.01and intangible assets). The finding of the study supportsAnghel et al (2018) andJasor et al (2013), who stated that IC has a positive effect on DER.The result also discovered that IC cannot moderate the effect of EPS on MVE. Several companies experienced a decline in IC use.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…2021.01and intangible assets). The finding of the study supportsAnghel et al (2018) andJasor et al (2013), who stated that IC has a positive effect on DER.The result also discovered that IC cannot moderate the effect of EPS on MVE. Several companies experienced a decline in IC use.…”
supporting
confidence: 85%
“…Thus, it will increase the company's MVE(Anghel et al, 2018). Previous research on IC and DER showed that IC has a positive effect on DER(Anghel et al, 2018;Jasor et al, 2013; Chang & Lee, 2012). Accordingly, it is hypothesized that DER affects MVE, with IC as a moderating variable.…”
mentioning
confidence: 94%
“…Fang and Lin (2010) and Wang (2011) in Taiwan found that the large-sized firms have increased performance. Besharati et al (2012) in Tehran and Jasor and Rezazadeh (2013) in Iran also supported similar findings. However, our results are contradictory with the results of Ho et al (2005).…”
Section: Results and Analysismentioning
confidence: 57%
“…The reason is that the greater the intellectual capital owned by the company, it will help the company to manage the level of debt that the company aims to increase investment and the smooth operation of the company. Research on intellectual capital and debt to equity ratio studied by Ameneh et al (2015) Chang & Lee (2012) Jasor et al (2013) Winahyu & Mimba (2018) show that intellectual capital has a positive effect on debt to equity ratio. H4: Debt to equity ratio affects market value of equity with intellectual capital as a moderating variable…”
Section: Debt To Equity Ratio and Market Value Of Equity Moderated By...mentioning
confidence: 99%